Urban rail station assessment model for transit oriented development in greater Kuala Lumpur - Abd Aziz, Sahrir (2022)
To make the city sustainable and comfortable for residents, the essence of development plans must be able to fill the present and future needs. Planning made just to fit the current need will create a big problem in the future. The government plans to upgrade the public transport system in the capital Kuala Lumpur by allocating large provisions. It has to be channeled in a way that is better for the greater good and long-term interests. In view of the many effects the railway transportation system contributed to Kuala Lumpur city, especially in terms of the development of the surrounding area, this research studies the correlation between the provision of the station and with development and growth of the surrounding vicinity. Organized planning pays off the large financial provisions by the Government. Research considers the development of stations or terminals must be correlated to the Transit-Oriented Development in which each station must meet or achieve a sustainable level of TOD. The research proposes a method to assess the level of achievement of a station that has been developed or is in the pipeline to be developed with the rating method. The research's objective is specifically to propose an urban rail station assessment model for station development toward TOD. The data was collected through a field survey and was subjected to statistically analysed through descriptive statistics, factor analysis, multiple and simple linear regression analysis using the Statistical Package for Social Sciences (SPSS) version 22 and interpreted to answer the research questions and the research objectives formulated to achieve the study. Rating given to a station depends on the resulting impact of the development and growth of the surrounding area. Reviewing the type of the resulting impact serves as the basis for planning the type of development to be made as objective by TOD. The development towards sectorial basis such as residential, commercial, or mixed development is a fundamental thing that is important for city residents' wellness